2021
DOI: 10.1002/ams2.645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social support on mental health for critical care nurses during the coronavirus disease 2019 (COVID‐19) pandemic in Japan: A web‐based cross‐sectional study

Abstract: Aim The aim of this study was to examine whether high social support has a protective effect on mental health for critical care nurses during the coronavirus disease 2019 (COVID‐19) pandemic. Methods This cross‐sectional anonymous web‐based survey was conducted from November 5 to December 5, 2020, in Japan and included critical care nurses. The invitation was distributed via mailing lists. Results Of the 334 responses that were obtained, 64.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Next to possible (speculative) cultural explanations, the Japanese sample differs from the other countries in that it is much smaller than the others, participants were paid for partaking in the study, the sample’s age was more evenly distributed (similar to France), and it is the only country where there was no strict lockdown (as reflected in the mobility and stringency indices in Table 2 ). Of note, in line with our results, other studies conducted during the pandemic period in Japan showed more pronounced levels of depression than anxiety [ 39 , 40 ], with mean HADS values similar to the ones reported in the present study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Next to possible (speculative) cultural explanations, the Japanese sample differs from the other countries in that it is much smaller than the others, participants were paid for partaking in the study, the sample’s age was more evenly distributed (similar to France), and it is the only country where there was no strict lockdown (as reflected in the mobility and stringency indices in Table 2 ). Of note, in line with our results, other studies conducted during the pandemic period in Japan showed more pronounced levels of depression than anxiety [ 39 , 40 ], with mean HADS values similar to the ones reported in the present study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Social support is a multidimensional concept that involves various aspects of resources one perceived that come from various sources, such as family, friends, and co-workers ( 39 , 40 ). An ever-growing number of studies and reviews have consistently documented the important protective role of social support on mental health and well-being ( 41 43 ). People with a higher level of social support have a lower level of psychological distress such as stress, depression, and anxiety ( 41 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…An ever-growing number of studies and reviews have consistently documented the important protective role of social support on mental health and well-being ( 41 43 ). People with a higher level of social support have a lower level of psychological distress such as stress, depression, and anxiety ( 41 43 ). Social support can promote mental health both directly as a main effect, and indirectly as a moderating variable that buffers the effects of stress ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when individuals have adequate social support, they may feel more emotional support and encouragement, which may enhance their ability to cope with work difficulties, which may make them more willing to stay in their current job rather than choose to leave ( 66 ). However, during the outbreak, Tatsuno et al ( 67 ) conducted a cross-sectional survey of ICU nurses in Japan, and the findings showed no relationship between social support and PTSD. This varies from our findings, where social support was not associated with psychological distress in the early stages and later stages in Cook and Bickman ( 68 ).…”
Section: Discussionmentioning
confidence: 99%